Can transparency and accountability programs improve health? Experimental evidence from Indonesia and Tanzania. (June 2021) - Arkedis, Jean; Creighton, Jessica; Dixit, Akshay; Fung, Archon; Kosack, Stephen; Levy, Dan; Tolmie, Courtney
Highlights: We assess the impact of a transparency & accountability program on health outcomes. We use randomized controlled trials involving 400 villages across Indonesia and Tanzania. On average, no evidence of a treatment effect on maternal and newborn healthcare. The causal paths from planning actions to tangibly improving healthcare were complex. Overall, few communities were able to traverse these complex causal paths. Abstract: We assess the impact of a transparency and accountability program designed to improve maternal and newborn health (MNH) outcomes in Indonesia and Tanzania. Co-designed with local partner organizations to be community-led and non-prescriptive, the program sought to encourage community participation to address local barriers in access to high quality care for pregnant women and infants. We evaluate the impact of this program through randomized controlled trials (RCTs), involving 100 treatment and 100 control communities in each country. We find that on average, this program did not have a statistically significant impact on the use or content of maternal and newborn health services, nor on perceptions of civic efficacy or civic participation among recent mothers in the communities where it was offered. These findings hold in both countries and in a set of prespecified subgroups. To identify reasons for the lack of impacts, we use a mixed-method approach combining interviews, observations, surveys, focus groups, and ethnographic studies that together provide an in-depth assessment of the complex causal paths linking participation in the program to improvements in MNH outcomes. Although participation in program meetings was substantial and sustained in most communities, and most attempted at least some of what they had planned, only a minority achieved tangible improvements, and fewer still saw more than one such success. In our assessment, the main explanation for the lack of impact is that few communities were able to traverse the complex causal paths from planning actions to accomplishing tangible improvements in their access to quality health care.